2000
DOI: 10.1159/000030116
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the Tyrosine Kinase Activity Growth Factor Receptors (EGFR, ERB B2, ERB B3) in Colorectal Adenocarcinomas and Adenomas

Abstract: The overexpression of three growth factor receptors: epidermal growth factor receptor (EGFR), ERB B2 and ERB B3 was evaluated immunohistochemically in 77 malignant and 15 benign colorectal neoplasms considering clinicopathological variables (histological structure, grade of differentiation, tumor localization, clinical stage of the disease). The relationship between the coexpression of EGFR-related proteins in individual patients was also evaluated. EGFR expression was revealed in comparable percentages of col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
89
2
7

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 204 publications
(102 citation statements)
references
References 26 publications
4
89
2
7
Order By: Relevance
“…Epidermal growth factor receptor is overexpressed in many different cancer types, including 60-80% of colon cancers (Porebska et al, 2000), which correlates with a poor prognosis (Mayer et al, 1993). This further supports the hypothesis that inhibition of the EGFR signalling cascade may potentially be therapeutic.…”
supporting
confidence: 57%
“…Epidermal growth factor receptor is overexpressed in many different cancer types, including 60-80% of colon cancers (Porebska et al, 2000), which correlates with a poor prognosis (Mayer et al, 1993). This further supports the hypothesis that inhibition of the EGFR signalling cascade may potentially be therapeutic.…”
supporting
confidence: 57%
“…For example, HER-2 overexpression was shown in 5.7-88.8% of non-small-cell lung cancers 10,11 and 3.0-54% of colon cancers. 12,13 To a smaller extent, this variability is also observed in amplification analysis. Different methods for analysis (Southern blot or fluorescent in situ hybridization (FISH)) and definitions of amplification have resulted in variable frequencies of amplification reported in the literature such as 0-66% in ovarian cancer 14,15 or 6-56.2% in breast cancer.…”
mentioning
confidence: 80%
“…Overexpression of the HER family members has been identified in a variety of human cancers such as gastrointestinal tract (Ghaderi et al, 2002;Kimura et al, 2004), colorectal (Hayashi et al, 1994;Porebska et al, 2000;Ooi et al, 2004), breast (Suo et al, 2002;Witton et al, 2003;Abd El-Rehim et al, 2004;DiGiovanna et al, 2005), lung (Hirsch et al, 2003), prostate (Di Lorenzo et al, 2002), and bladder cancers (Chow et al, 2001;Wester et al, 2002), and is correlated in a wide variety of tumours with the progression (Yarden and Sliwkowski, 2001). In particular, we and others have recently reported that the overexpression of EGFR of oesophageal SCC, partially accounted for by gene amplification, is found in 50 -70% (Itakura et al, 1994;Hanawa et al, 2006), and is indicative of a poor prognosis (Ozawa et al, 1989;Yano et al, 1991).…”
mentioning
confidence: 99%